Effectiveness of Independent Curriculum in Improving Student Learning Motivation Class V on PKN Lessons at SDN 064965 Sidodame City of Medan - Naibaho, Feby Sulastri (Journal of General Education Science, 2024)
This study aims to determine the effectiveness of the implementation of the Independent Curriculum in increasing the learning motivation of fifth-grade students in Civics at SDN 064965 Sidodame , Medan City. The background of this study is based on the important role of the curriculum as a reference in the learning process, where the Independent Curriculum is presented as an effort to restore post-pandemic learning with a more flexible, student-centered approach, and prioritizing student interests and talents. This study uses a descriptive qualitative approach with observation, interviews, and documentation methods. The subjects in this study were class teachers and fifth-grade students. The results show that the implementation of the Independent Curriculum has a positive influence on increasing student learning motivation. Students become more active, creative, and enthusiastic in participating in Civics learning. However, in its implementation, several challenges remain, such as teachers' limited understanding of the new curriculum and a lack of supporting facilities and infrastructure. Nevertheless, in general, the Independent Curriculum has proven quite effective in building student learning motivation through an approach that is fun, contextual, and appropriate to the needs and potential of individual students.